Pediatric gastrointestinal disease : pathophysiology, diagnosis, management - Walker, W. Allan (Decker, 2000)
Harvard School of Public Health, Boston, MA. Reference text for pediatric gastroenterologists. This edition commemorates the convening of the first World Conference, held in Boston in August 2000. System requirements are not cited
Keywords: Infant; Digestive System Diseases; mladiství; gastroenterologie; Adolescent; dítě; pediatrie; Child; nemoci trávicího systému; kojenec